2015
DOI: 10.1016/j.jcrs.2014.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen therapy for corneal edema after cataract surgery

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In 2015, Sharifipour et al reported that supplement trans‐corneal normo‐baric oxygen therapy at a flow rate of 5 L/min for 1 hr twice daily after cataract surgery decreased corneal oedema more rapidly than medical therapy and systemic oxygen therapies and preserved more endothelial cells. The authors suggest that trans‐corneal oxygen mitigates the damage to endothelial cells before permanent loss occurs, thus improving endothelial pump function and decreasing corneal oedema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, Sharifipour et al reported that supplement trans‐corneal normo‐baric oxygen therapy at a flow rate of 5 L/min for 1 hr twice daily after cataract surgery decreased corneal oedema more rapidly than medical therapy and systemic oxygen therapies and preserved more endothelial cells. The authors suggest that trans‐corneal oxygen mitigates the damage to endothelial cells before permanent loss occurs, thus improving endothelial pump function and decreasing corneal oedema.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in pump function can lead to corneal oedema and to a reduced ability to clear existing excess fluids (Waring et al 1982). A recent study showed that supplemental trans‐corneal oxygen therapy after cataract surgery led to a more rapid resolution of corneal oedema when compared to medical therapy (topical steroids and sodium chloride 5% eye drops) and systemic oxygen therapy, and preserved more endothelial cells (Sharifipour et al 2015). The authors suggested that trans‐corneal oxygen mitigates the damage to the endothelial cells before permanent loss occurs, thus improving overall pump function and decreasing corneal oedema.…”
Section: Introductionmentioning
confidence: 99%
“…Although many cases with positive results have been published, clear evidence of its positive effect is scarce 18 - 20 . Another rarely used alternative is systemic or local oxygen therapy as proposed by Sharifipour, et al 15 , 16 . In our case, we obtained good results by adding to the medical management both the use of the amniotic membrane and oxygen therapy using masks or cameras over the eye.…”
Section: Discussionmentioning
confidence: 99%
“…One week after the burn, one-hour daily 100% oxygen therapy via a face mask at 10 L/min was started (16 sessions). Besides, six sessions of 5 L/min of oxygen application were performed on the right eye with a camera made for that purpose 15 , 16 . Twenty days after the burn, the amniotic membrane had been almost completely reabsorbed, with only a remnant observed on the temporal conjunctiva, and 95% of the cornea was epithelialized with only two remaining areas with fluorescein staining ( figure 4 ).…”
Section: Clinical Casementioning
confidence: 99%
“…Nevertheless, from the perspective of clinical practice, there are inevitably some postoperative complications after surgery [16]. Corneal edema is a common postoperative complication [17], and studies showed that postoperative adjustment by combining traditional Chinese medicine can improve the effect of cataract treatment [18]. Some plateau herbs have been found to be effective in treating cataract.…”
Section: Introductionmentioning
confidence: 99%